NUCLEAR ENERGY - Jurakulov, S.Z. (Educational Research in Universal Sciences, 2023)
Nuclear power is the most important sub-sector of the world energy industry, which began to make a significant contribution to the world’s electricity production several decades ago. Today, the price of electricity produced by nuclear power plants allows us to talk about serious competition with other types of power plants. A clear advantage of nuclear power plants is the absence of aerosol and greenhouse gas emissions into the atmosphere.